Effects of dam fear and stress on metrics of puppy welfare in commercial breeding kennels - Aynsley C. Romaniuk; Shanis Barnard; Traci Shreyer; Candace Croney (Scientific Reports)
Abstract It is well established that maternal factors can affect the abilities of offspring to cope with stressors and can influence their overall welfare states. However, maternal effects have not been extensively explored in US commercial breeding kennels (CBKs). Therefore, the objective of this study was to identify if fear and stress in dams affected puppy welfare metrics in CBKs. Bitches (n = 90) were tested at 6 weeks prepartum (6 W Pre), and again with their puppies (n = 390) at 4 (4 W Post) and 8 weeks (8 W Post) postpartum. Dams and puppies underwent stranger approach and isolation tests, and their feces were collected to measure fecal glucocorticoid metabolite (FGM) and secretory immunoglobulin A concentrations. Further, dams’ hair cortisol concentrations (HCC) were analyzed at the previously mentioned time points and at 1 week prepartum. Finally, birth and weekly weights were collected from puppies, and litter health metrics were recorded. Data were analyzed using mixed-effects and simple linear regression models. There were significant positive associations between dams’ exploration and stationary durations and puppies’ durations of the same respective behaviors during the isolation tests (exploration: $$\:\text{{\rm\:X}}$$ 2 (1) = 9.472, p = 0.002; stationary: $$\:\text{{\rm\:X}}$$ 2 (1) = 5.226, p = 0.022), 8 W Post dam FGMs and 8 W Post puppy FGMs (estimate: 0.0003, SE = 0.0001, p = 0.002), and 4 W Post dam HCCs and 4 W Post litter FGMs (estimate: 0.052, SE = 0.025, p = 0.053). Significant negative associations between 6 W Pre dam HCCs and 8 W Post puppy FGMs (estimate: -0.021, SE = 0.007, p = 0.007), puppies’ birth weights ( $$\:\text{{\rm\:X}}$$ 2 (1) = 3.908, p = 0.048), and puppies’ average weekly weight gains ( $$\:\text{{\rm\:X}}$$ 2 (1) = 0.111, p = 0.739) were also found. These findings suggest that indicators of dam fear and stress may be associated with potential indicators of puppies’ welfare states in CBKs. Findings provide new knowledge on fear and stress-related factors that may be used to support the welfare of dams and puppies in CBKs and other populations.